Modern pedagogical technologies of teaching foreign languages (Journal of Educational Sciences, 2023)
АNowadays there are various pedagogical technologies in modern foreign languages teaching methodology. In this article the author investigates an important category of methodic - teaching technologies. We know that the combination of such components of the methodical system as techniques, organizational forms and teaching aids form a teaching technology. In modern science teaching technology is seen as the fourth revolution after the creation of schools, the use of the written word in teaching and the invention of printing. Today the attention of many teachers is drawn to modern teaching technologies. Advances in science allow many interesting technologies to be introduced into teaching practice. In the article the author divides modern pedagogical technologies into groups. The article deals with communicative, personality-oriented, computer, intensive, socio-cultural pedagogical technologies of teaching foreign languages. Such a subdivision of various technologies became possible due to certain characteristic of certain technologies. Examples are given of how different scientists and Methodists from abroad use different pedagogical technologies in their countries. The research results of articles by foreign authors, to which the author came, are described in this article. A survey on the subject of possession of pedagogical technologies and methodical competence for master students was conducted in the empirical part of the article. It has been established that, on the one hand, master students have an advantage in information about modern pedagogical technologies; on the other hand, master studentsexperience certain difficulties in independent applying the latest technologies in the real educational process. It is recommended to increase laboratory practical classes on the methodic of teaching foreign languages in the cycle of training in the magistracy, during which students would have the opportunity to improve their methodical abilities and consolidate the studied material.Key words: English, educational technology, communicative technology, personality-oriented technology, socio-cultural technology, computer technology, intensive technology.